Implementasi Protokol Zigbee Pada Wireless Sensor Network - Jefri Muhrimansyah; Rakhmadhany Primananda; Kasyful Amron (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
WSN was implemented in densely populated area by using zigbee as the communication protocol. It was chosen to be the communication protocol because it is applicable in the extreme area. The selection of mesh topology due to each node is connected to each other, so they can communicate and switch the information among them. The selection protocol of routing Ad-hoc On-Deman Distance Vector (AODV) due to the route search on AODV is only needed when the route request is exist. In this research, testing was done in three scenarios, namely, test based on the condition where the barrier is exist and is not exist, test based on distance and the amount of the data. Based on the test, the analysis of several test parameters, such as throughput, delay and packet loss. Based on the result of testing and analyzing the Zigbee maximum distance in sending the data censor was 40 meter in a barrier condition, with the highest throughput value was 72 bps, the highest delay value was 0,0028 ms and the highest packet loss value was 70% at 50 meter distance. On the amount of data based testing, the highest throughput value was 65.3 bps, the highest delay value was 3.872ms, and the highest packet loss value was 47% from 30 data. Furthermore, the condition with and without barrier based test resulted some values, such as the highest throughput value was 65.3 bps, the highest delay value was 3.136ms and the highest packet loss value was 35%.